Recent advances in GABAB receptors: from pharmacology to molecular biology. - Ong Jennifer; Kerr David Ib (Acta Pharmacologica Sinica; Vol 21, No 2 (February 2000): Acta Pharmacologica Sinica, 2016)
Bicuculline-insensitive receptors for the inhibitory neurotransmitter gamma-aminobutyric acid (GABA), GABAB receptors, are a distinct subclass of receptors that mediate depression of synaptic transmission and contribute to neuronal inhibition. When activated, these receptors reduce transmission at excitatory and inhibitory synapses, as a result of an increase in K+ conductance, or a decrease in voltage-dependent Ca2+ currents. They are also linked to G-proteins, or intracellular effector systems in a very complex manner. The recent development of highly specific and potent agonists and antagonists for these receptors has led to a much better understanding of their physiology and pharmacology, including their heterogeneity, as well as their molecular biology. Over the past year, expression and cloning studies have contributed to major advances in characterizing GABAB receptor structure, with the discovery of the amino acid sequences of GABABR1a/R1b splice variants and GABABR2 receptors. These isoforms are widely distributed throughout the nervous system, and can be functionally expressed. Importantly, GABABR2 receptors can form a heteromeric assembly with GABABR1 proteins to operate as a heterodimer that displays robust coupling to inward-rectifying K+ channels, as well as inhibition of forskolin-stimulated adenylate cyclase activity. Further insights underlying the mechanisms of GABAB receptor functions can now be gained, leading ultimately to the therapeutic potential of drugs acting at these sites. It is increasingly clear that new information on GABAB receptor molecular structure will provide a plethora of targets for pharmaceutical intervention in areas such as drug addiction, nociception and absence seizures. This review summarizes the renewed efforts, and highlights the recent advances emerging in this field.